“Nothing but Gratitude…”. Plutarch, Cavafy, Shakespeare, Brodsky* - Eloeva, Fatima A. (Literatūra, 2025)
This article examines Joseph Brodsky’s poem I Entered the Cage Instead of a Wild Beast… in the context of intertextual and cultural traditions spanning Plutarch, Shakespeare, and Constantine Cavafy. The focus lies on the theme of gratitude as it evolves from Plutarch’s Life of Antony, through Shakespeare’s Antony and Cleopatra, into Cavafy’s reinterpretations, and finally Brodsky’s autobiographical poetry. The study applies reception theory and intertextual analysis to highlight how Brodsky’s verse redefines the ancient theme of dignity in defeat as a modern affirmation of gratitude.